82.7k views
1 vote
Which expression is equivalent for this

Which expression is equivalent for this-example-1

1 Answer

1 vote

Answer: Option A

Explanation:

Remember that


+ * - = -\\- * + = -\\+ * + = +\\- * - = +\\

We have the expression


(1)/(2)x + (-7)-2*(1)/(4)-(-2)

Solve first the multiplication of signs


(1)/(2)x + (-7)-2(1)/(4)x-(-2)\\\\(1)/(2)x -7-2(1)/(4)x+2\ \ \ \ \ \ \ \ Note:\ 2(1)/(4)=2+(1)/(4)=(9)/(4)\\\\(1)/(2)x -(9)/(4)x-7+2\ \ \ \ \ \ \ \ Note:\ (1)/(2)-(9)/(4)=-(7)/(4)=-1(3)/(4)\\\\-1(3)/(4)x -5

User Mathinvalidnik
by
5.4k points